Sea Power as National Defence: Has Indonesia implemented it? - Dyah Sekar Arum; Jonni Mahhroza; Lukman Yudho Prakoso; Tasdik, Tasdik; Sri Patmi (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The objective is to analyze the role of maritime defense in Indonesia's national strength and alliances, examining modern naval capabilities, regulations, investment, and Mahan's Sea Power principles for strategic readiness and economic integration in the 21st century. The research employs a descriptive qualitative method, focusing on in-depth understanding and data interpretation. Triangulation is used for data validity, and analysis follows an inductive approach without generalization. Additionally, it utilizes sea power theory and defense diplomacy concepts to explore Indonesia's maritime strength and diplomatic efforts. Sea Power is an important issue for all countries in the world. Several maritime conflicts have gotten out of control due to a lack of input regarding naval defence strategies. Such as conflicts over the dynamics of China's militarisation in the South China Sea (LCS) region or the Russia-Ukraine Black Sea conflict. Considering Indonesia as a maritime country that is required to immediately provide national defence in the future, to prevent future conflicts, following the application of sea power, Indonesia is considered to have achieved the criteria in this matter. Therefore, through the application of Alferd Thayer Mahan's "Sea Power" theory, researchers try to adapt this theory to several Indonesian efforts in the 21st Century with an interest in highlighting the Indonesian Navy's efforts and strategies in achieving contemporary sea power in the 21st century. With a focus on research into Indonesia's national interests in achieving sea power and Indonesian naval strategy. With the results, it is hoped that readers will be able to realize the importance of the sea and find out to what extent Indonesia has implemented Mahan's theory by examining the two superpower countries, the US and China, which are countries that have applied this theory to their navies